International Intraductal Papillary Mucinous Neoplasms Registry: Long-Term Results Based on the New Guidelines. Issue 3 (March 2017) - Moris, Maria; Raimondo, Massimo; Woodward, Timothy A.; Skinner, Verna J.; Arcidiacono, Paolo G.; Petrone, Maria C.; De Angelis, Claudio; Manfrè, Selene; Carrara, Silvia; Jovani, Manol; Fusaroli, Pietro; Wallace, Michael B.
Abstract : Objective: The aim of this study was to analyze the outcomes of a long-term intraductal papillary mucinous neoplasm (IPMN) registry and evaluate new guidelines. Methods: A prospectively maintained IPMN registry involving 6 centers in Europe and the United States was used to collect the data. Patients with more than 1-year follow-up and no malignancy diagnosed within the first 3 months of surveillance were included. Results: From 1999 to 2014, 620 patients were included. The median follow-up time was 3 years. Thirty-seven (6%) patients developed malignancy with a median time from IPMN diagnosis to malignancy of 10.3 months. The 1-, 5-, and 10-year actuarial rates of disease-free survival were 97%, 93%, and 92% respectively. Four hundred thirty-one patients met criteria for low-risk branch duct IPMN consisting of cyst size less than 3 cm, with no solid component or main duct dilation. Eight malignancies were diagnosed in this subgroup, all of them within the first 5 years. From this subcohort, 112 patients had a follow-up time of more than 5 years, and no malignancy was diagnosed. Conclusions: In IPMN lesions with low-risk features at baseline, the risk of progression to malignancy after the first 5 years of follow-up was minimal. Furthermore, the main cyst characteristics remained unchanged during their surveillance. Abstract : Supplemental digital content is available in the text.